STUDI LITERATUR ANALISIS IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH DASAR - Syintia Kamilasari; Widi Sukma Nugraha; Siti Nurkamilah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of the Kurikulum Merdeka (Independent Curriculum) in primary schools-covering implementation forms, supporting factors, obstacles, and impacts on the learning process-through a literature review approach. The study employs a qualitative literature review method. Data were gathered from relevant national scholarly journal articles, books, and official documents regarding the implementation of the Kurikulum Merdeka in primary schools, published between 2021 and 2025. The data were analyzed using the Miles and Huberman model, comprising data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the Kurikulum Merdeka has a positive impact on the quality of learning in primary schools. The application of differentiated instruction, flexibility in developing instructional materials, and character strengthening through the Projek Penguatan Profil Pelajar Pancasila (P5)-or the Project to Strengthen the Pancasila Student Profile-have successfully enhanced students' active participation, creativity, critical thinking skills, and independence. However, the implementation of the Kurikulum Merdeka still faces various challenges, including uneven teacher readiness, limited facilities and infrastructure, and the need for continuous training and mentoring. Therefore, support from the government, schools, and teachers is essential to enhance the effectiveness of the Kurikulum Merdeka implementation, ensuring that the goal of improving learning quality in primary schools is optimally achieved. Keywords: implementation of the Merdeka Curriculum, elementary school, literature review, differentiated instruction, Project to Strengthen the Profile of Pancasila Students.